Conceptualising the intrinsic and extrinsic push factors influencing international edu-tourists decision to study abroad: the Malaysia perspective - Ojo, Bello Yekinni; Raja Yusof, Raja Nerina; Ab Aziz, Yuhanis; Awang, Khairil Wahidin (Australian Academy of Business and Social Sciences, 2014)
This article conceptualised the intrinsic and extrinsic factors that influence international edu-tourists from the emerging economy to study in an emerging economy like Malaysia. A growing body of models has been developed to explain the factors influencing international edu-tourist from the emerging economies to choose to study abroad in the developed economy. In view of the new mobility trend of the international edu-tourists from the emerging economies to study abroad in an emerging country, including, limited model to explain this new mobility trend in Malaysia, this article contributes to the Malaysia literature pertaining to this subject. The article proposes 4 intrinsic and 2 extrinsic antecedent variables in predicting the new mobility behaviour of the international edu-tourists from the emerging economies who chooses to study abroad in Malaysia (an emerging economy). The limitations of this article stem from the nature of the study itself. Being a preliminary study, it integrated the factors identified in the existing literature. Thus, future empirical research on this subject is required to examine the existing relationships among the aforementioned factors, by giving and analyse the weight of each factor influencing the choice to study abroad in an emerging economy by the international edu-tourists from the emerging countries. Therefore, determining the relative importance of each element and factors that constitute an important source of information for future work in international edu-tourism studies.